Exploratory study for the development of happiness management in Spanish SME by external consultants. - Molina-Gómez, Jesús; Mercade-Mele, Pere; Rastrollo-Horrillo, María Ángeles; Núñez-Sánchez, José Manuel (My University, 2023)
This exploratory study is based on a consultancy research project which arises as a response to the current trend, still incipient in the Spanish market, to implement well-being and happiness programs in companies. The main objective of the research is to define a proposal for a certificate of happiness management in Spanish SMEs, with the help of external consultants. In order to achieve this objective, a mixed method, quantitative and qualitative, has been used to triangulate the results, thus enriching the research. It has also been divided into sequential phases, beginning with a thorough literature review, followed by the analysis of the quantitative study to determine the level of happiness of workers in the country. Semi-structured in-depth interviews with expert practitioners were also conducted, which have helped to improve the proposal, highlighting, among other issues, the importance of being a socially responsible company, promoting internal and external happiness. The result has been a proposal for a consulting process to obtain a Quality Management Certificate. in SMEs. This reinforces the contribution of management consulting in the generation of useful and innovative knowledge for SMEs, which could allow them, not only to improve the happiness of their employees, with all the advantages that this entails, but also to enhance their competitive position. This will also help to bridge the gap detected between large companies and SMEs when it comes to being able to access a certified happiness management, without the need for a heavy and costly structure, but with the help of expert consultants.
Keywords: Gestión de personal; Condiciones de trabajo - Gestión; Well-being; Certification; Consulting; Happiness management; Human resources; Small and medium enterprises